Late-time near-infrared evolution of the ejecta and the equatorial ring of Supernova 1987A - Ahola, Antero (fi=Turun yliopisto|en=University of Turku|, 2018)
Supernova 1987A, located 50 kpc away in the Large Magellanic Cloud, is the closest supernova (SN) observed in the time of modern astronomy. The circumstellar medium of SN 1987A is characterised by a system of three rings ejected by the progenitor star some 20,000 years ago. The innermost of the rings, the equatorial ring (ER), started brightening strongly across the spectrum when the SN ejecta struck it around 1995. The impact gave rise to brightly glowing hotspots along the ring. Studying the ER and its interaction with the ejecta will give us insight on the nature of the SN progenitor star. This thesis examines the ER and the ejecta using aperture and point spread function photometry and image subtraction. The images, taken between 1997 and 2017, are in the near-infrared wavelengths (~0.8-2.4 µm). The imaging data are from the Hubble Space Telescope and the European Southern Observatory Very Large Telescope. Based on the near-infrared photometry, the ER reached maximum brightness around 2011-2013 and has since started fading. Most of the ring emission appears to come from the hotspots. The brightening of the ring and the expansion of the ejecta was found to be asymmetric, requiring asymmetries in the explosion, circumstellar medium, or both. Future observations will be of interest as SN 1987A is still evolving. Extrapolating from the photometry, the ring is expected to fade away in ~2020. In addition, the compact object left from the SN explosion still remains undetected.